2021
DOI: 10.1021/acs.chemmater.1c01170
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Activation Barriers for Lithium-Ion Conductivity through Orientational Disorder in the Cyanide Argyrodite Li6PS5CN

Abstract: Rapid advancements in safe and high-energy-density energy storage are predicated on identifying new solid-state ion conductors with low activation energies and high ionic conductivities for all-solid-state battery technologies. Halide argyrodites are among some of the top candidates for solid-state electrolytes, as they can achieve ionic conductivities that approach liquid electrolytes. Incorporating dynamic pseudohalide species in argyrodite solid electrolytes presents an exciting opportunity to exploit latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…A recent example is Li 6 PS 5 CN, where the CN − group takes the place of the original Cl sites for the "paddle-wheel" effect on Li conductivity. 11 Turning to the borohydride, Sakuda et al has reported the synthesis of argyrodite structure Li 6 PS 5 (BH 4 ) via a two-step ball-milling method. 9 Subsequently, Dao et al used a one-step ball-milling method to introduce a small amount of BH 4 − in the argyrodite Li 6 PS 5 Cl 1−x (BH 4 ) x (x = 0.17) and increased the ionic conductivity compared to Li 6 PS 5 Cl.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent example is Li 6 PS 5 CN, where the CN − group takes the place of the original Cl sites for the "paddle-wheel" effect on Li conductivity. 11 Turning to the borohydride, Sakuda et al has reported the synthesis of argyrodite structure Li 6 PS 5 (BH 4 ) via a two-step ball-milling method. 9 Subsequently, Dao et al used a one-step ball-milling method to introduce a small amount of BH 4 − in the argyrodite Li 6 PS 5 Cl 1−x (BH 4 ) x (x = 0.17) and increased the ionic conductivity compared to Li 6 PS 5 Cl.…”
mentioning
confidence: 99%
“…Therefore, it has been proposed to introduce the borohydride group into the halogen position of Li-argyrodite to improve the ionic conductivity. , This is because the rotational motion (the so-called “paddle-wheel” effect) of the polyanions could significantly accelerate the hopping of Li cations in the lattice. A recent example is Li 6 PS 5 CN, where the CN – group takes the place of the original Cl sites for the “paddle-wheel” effect on Li conductivity . Turning to the borohydride, Sakuda et al has reported the synthesis of argyrodite structure Li 6 PS 5 (BH 4 ) via a two-step ball-milling method .…”
mentioning
confidence: 99%
“…Therefore, any ionic-conducting structures that can accommodate halogen site can be potential candidates for such a strategy. Indeed, we have seen this realized experimentally in Li/Na-rich antiperovskites (Li/Na) 3−x (O/S)X (X = halogen or cluster) 40 , 41 and lithium argyrodites 42 , 43 . More recently discovered solid electrolyte systems with good properties, such as Li x ScCl 3+x 37 , Na 3−x Y 1−x Zr x Cl 6 44 and Na 3−y PS 4−x Cl x 45 , can be also subject to such a strategy.…”
Section: Discussionmentioning
confidence: 82%
“…The new argyrodite Li 6 PS 5 CN containing orientationally disordered cyanide ions exhibited a relative low lithium ion migration barrier, though it adopting the similar crystal structures with Li 6 PS 5 Br (Figure 8e). [106] This strategy could be innovatively applied in ionic conductors for multivalent metal ions. Yan et al predicted NH 3 in Mg(BH 4 ) 2 NH 3 exchanged and constructing a highly flexible structure, profiting from the di-hydrogen bonds and dramatically improving the Mg-ion conductivity ≈8 orders of magnitude higher than that of Mg(BH 4 ) 2 (Figure 8f).…”
Section: Structural Disorder or Distortionmentioning
confidence: 99%
“…e) Crystal structure of the cyanide argyrodite Li 6 PS 5 CN with orientationally disordered cyanide ions. Reproduced with permission [106]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%